EMS-based environmental regimes as club goods: examining variations in firm-level adoption of ISO 14001 and EMAS in UK, US and Germany - Kollman, Kelly; Prakash, Aseem (2002)
This paper examines variations in firm-level adoption of environmental management systems (EMS) - ISO 14001 and the European Union"s Eco-Audit and Management Scheme (EMAS) - in the United Kingdom. Germany and the United States. Drawing on insights from club theory, institutional theory, and stakeholder theory, it argues that despite the fact that these EMS are created by supranational organizations (one regional and one international), firms' perceptions of their costs and benefits are largely determined by domestic factors. In particular, these perceptions are shaped by how EMS are promoted and information about them is disseminated in each country (supply aspects) and how the constellation of stakeholders (suppliers, environmental groups, regulators, general public) support their introduction (demand aspects). The paper concludes that there are numerous ways governments and interested stakeholders can encourage companies to adopt voluntary environmental codes. The key is to find the right mix of incentives for specific national contexts. - Reproduced.
Keywords: Environmental management